Feasibility Analysis of Information Technology Investment Using Cost Benefit Analysis Method - Riza Prapascatama Agusdin; Naufal Nur Aidil (Telematika, 2022)
Objective: One of the strategies that companies can do to survive amid fierce business competition is to invest in IT. Currently all companies need to invest in IT to improve company performance better but usually the budget costs that must be incurred by companies to make IT investments are very large. Therefore, it is necessary to analyze the feasibility of IT investment. This study aims to determine how much the costs incurred and the benefits obtained after creating a Social Media Analysis information system and also to find out whether the Social Media Analysis information system development project is feasible or not.Methods: This study uses the Cost Benefit Analysis method where the method compares the components of costs and benefits which are then recommended for a policy on investment projects. The Cost Benefit Analysis method is supported by several calculation criteria such as Net Present Value (NPV), Payback Period (PP), Return On Investment (ROI), and Benefit Cost Ratio (BCR).Results: The results showed that the NPV for 5 years was Rp. 300,138,606, PP was 2 years and 11 months, ROI was 9.03%, and BCR was 1.08. From the results of this study, it can be concluded that the Social Media Analysis information system investment project is feasible to continue.